HESPERIIDAE FAMILY (LEPIDOPTERA): SPECIES DIVERSITY IN A PRESERVED CAATINGA FRAGMENT IN THE SERTÃO OF ALAGOAS, BRAZIL (REMUNOM, 2025)
The Caatinga, a biome found exclusively in Brazil, harbors great biodiversity and high endemism, with species adapted to dry conditions and strong environmental seasonality. Among these species, butterflies—such as those from the Hesperiidae family—stand out as environmental bioindicators due to their sensitivity to ecological disturbances. Additionally, they act as pollinators that contribute to nature conservation. In this context, the present study aimed to investigate the species diversity of skippers in a preserved fragment of Caatinga and to infer the possible ecological roles of these species within the ecosystem. The research was conducted in the “Serra da Camonga,” located in the municipality of Santana do Ipanema, in the semi-arid region of the state of Alagoas, in Northeastern Brazil. The methodology consisted of collecting individuals, identifying, and cataloging the species based on taxonomic characteristics. As a result, three species were recorded: Urbanus dorantes dorantes, Urbanus proteus, and Urbanus teleus. These butterflies share common adaptations, such as high flight speed, which facilitates predator evasion and exploration of different areas, and hook-shaped antennae that help detect odors and environmental stimuli. These characteristics make them effective bioindicators of disturbed environments. The low number of species found may be related to the survival challenges imposed by the biome's conditions, such as long dry periods and climatic seasonality, which compromise the vegetation used for shelter and food. Thus, the data obtained reinforce the importance of conserving Caatinga fragments, especially in the face of environmental threats that directly affect local biodiversity.